Investigation of secure VEKIT web interface for preventing environment pollution - Balaji, Kumar; Selvam, Muthusamy (Transport, 2020)
This paper describes a new system – Vehicle Kit (VEKIT), which uses a secure web-based interface for the authentication and monitoring of Vehicular Ad-Hoc Network (VANET) infrastructure and for preventing environment pollution. This paper presents the hazards caused by the usage of bags made of plastic material and proposes the design of VEKIT, which is to be installed in the vehicles for reducing the usage of such carry bags up to 75%. The survey results prove that the proposed VEKIT approach is very much relevant to solve the pollution problem faced by various countries. This novel application adds value to the future VANET projects by helping the countries to prevent pollution. The web interface of VEKIT presented in the paper can also be used to monitor the vehicles for their authenticity. A secure architecture is proposed for the usage of VANET in transport related projects.First published online 1 September 2020